In Situ Visualization of Interfacial Sodium Transport and Electrochemistry between Few‐Layer Phosphorene. Issue 10 (15th May 2019) - Zhu, Chongyang; Shao, Ruiwen; Chen, Shulin; Cai, Ran; Wu, Yi; Yao, Libing; Xia, Weiwei; Nie, Meng; Sun, Litao; Gao, Peng; Xin, Huolin L.; Xu, Feng
Abstract: For rechargeable batteries, ionic transport within the electrode materials is a critical process that controls the rate capability and energy efficiency of the battery. Despite substantial studies, the atomistic observation of the interfacial ionic transport and electrochemical reactions occurring between the solid‐state electrodes is lacking. Here, in situ transmission electron microscopy (TEM) is used to deliberately design an unusual sample configuration, enabling dynamic observation of the sodium ionic transport within a single‐crystal nanostructure and between different few‐layer phosphorene nanosheets. An unhindered and reversible ionic shuttling between few‐layer phosphorene is directly observed in real time. In addition, it is found that sodium transport kinetics are closely related to the interface orientation and the intimate contact between solid electrodes plays a significant role in inhibiting dendrite growth. Furthermore, by fast TEM imaging with ≈40 ms resolution a unique stripe‐like sodium transport behavior is observed in phosphorene, and the multiple sodium ionic transport pathways at the interfaces with atomic spatial resolution are revealed. This work may supply enlightening insights into understanding the solid–solid interfacial electrochemistry between electrode materials. Abstract : Solid–solid interfacial sodium ionic transport between few‐layer phosphorene nanosheets is revealed by state‐of‐the‐art in situ transmission electron microscopy technique. Unique stripe‐like sodium transport behavior in phosphorene and multiple sodium ionic transport pathways at the interfaces are directly revealed with atomic spatial resolution, which may provide enlightening insights into understanding the solid–solid interfacial electrochemistry between electrode materials.